Early verb production in Nungon - Sarvasy, Hannah S. (Frontiers in Psychology, 2023)
This brief research report presents a comparison of the early verb productions of four children acquiring the Papuan language Nungon as a first language. A previous case study examined only verb productions of the child TO; these are now compared with those from three other children, studied from ages 1;1-2;7 (non-dense corpus; one child, AB) and ages 2;4-2;7 (dense corpora; two children, MK and MF). Two of the most striking features of TO's early verb productions are shown to be outliers relative to the other three children: her 'root nominals' stage and her delayed near future tense production. Neither of these is transparently linked to patterns in her parents' childdirected speech. The other children also display differing strategies into language production. The dense corpus is beneficial for catching tokens of less-frequent inflections, but the frequent long recording sessions may be difficult for at least one child to tolerate.